Labor-intensive public works for food security: Experience in Africa - von Braun, Joachim; Teklu, Tesfaye; Webb, Patrick (International Food Policy Research Institute, 1991)
Labor intensive public works program, a key instrument for addressing food security problems, are widely applied in Asia and were commonly utilized by today's industrialized countries, for example, during economic crises, for example, in the eighteenth century and during the 1920s and 1930s. Yes, until recently, they were rarely used in sub-Saharan Africa. This report reviews the experience with labor-intensive public works programs in Africa and identifies potentials for such program to improve food security of target population groups. The information generated leads to preliminary policy conclusions, strategy formulation, and program design for reducing hunger and malnutrition.